A taxonomic study of the genus Bagdadia Amsel, 1949 from Hainan Island of China (Lepidoptera: Gelechiidae) - Yang, Meiqing; Li, Houhun (Zootaxa, 2015)
Five species of the genus Bagdadia Amsel are recognized from Hainan Island of China in this paper, of these, Bagdadia khaoensis (Park & Ponomarenko) comb. nov. is proposed, and it is reported for the first time from this country. One new species, Bagdadia tricornis sp. nov. is described and one possibly new species is discussed but not formally named for lack of material. Adults and genitalia of the new and the unnamed species are illustrated and a key to known species of the genus from China is provided.